ANALISIS KEPUASAN MAHASISWA DITINJAU DARI KINERJA DOSEN DAN FASILITAS PEMBELAJARAN - Ridwan Idris; Hamsiah Djafar (Universitas Islam Negeri Alauddin Makassar, 2019)
This study aims to study the level of student satisfaction in terms of the ability of lecturers and learning facilities in the Department of Islamic Education Management of the Faculty of Tarbiyah and Teacher Training UIN Alauddin Makassar. This research is a quantitative descriptive with employing survey model. The population in the research was 243 people with 24 sample. The data were collected using a questionnaire with Likert Scale. The results showed that the satisfaction of MPI students in terms of lecturer performance was satisfactory category, based on four indicators: learning planning in the satisfactory category, the implementation of learning was very satisfying category, learning outcomes was quite satisfactory category, and guidance and direction was unsatisfactory category. MPI Study Program student satisfaction in terms of Learning facilities in the category was quite decisive, based on four indicators: lecture rooms according to the category are quite satisfactory, chairs and desks are less satisfactory, blackboards/blackboards were quite satisfactory, and learning media were quite satisfactory.